2015
DOI: 10.1155/2015/270508
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Therapy in Patients with Acute Coronary Syndrome in the Intermountain Heart Collaborative Study

Abstract: Objective. To determine factors associated with single antiplatelet (SAP) or dual antiplatelet (DAP) therapy and anticoagulants (AC) use in hospital and after discharge among patients with acute coronary syndrome (ACS). Methods. We evaluated 5,294 ACS patients in the Intermountain Heart Collaborative Study from 2004 to 2009. Multivariable logistic regressions were used to determine predictors of AC or AP use. Results. In hospital, 99% received an AC, 79% DAP, and 19% SAP; 78% had DAP + AC. Coronary stents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Consequently, bleeding risk is one of the most important limits and discomforts in long-term VKA treatments [11,12,13]. The numerous indications for VKA therapy [6,9,14,15,16] are reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, bleeding risk is one of the most important limits and discomforts in long-term VKA treatments [11,12,13]. The numerous indications for VKA therapy [6,9,14,15,16] are reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Warfarin was prescribed in 2.1% of patients at discharge. The use of DAPTs is associated with a lower incidence of major CV events and bleeding complications compared with the use of SAPT 18 . A review reported that use of DAPT with clopidogrel and aspirin reduced the risk of CV death, MI, or stroke to a significant extent ( p = 0.031) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The overall equalization of outcomes among AT strategies, in this interpretation, indicates the aggregate success of these clinical decisions. The clinical decision making process involves a myriad of individual patient clinical factors, but also includes current guidelines and recommendations [Zeymer et al 2013; Knight et al 2015]. In our study of ACS patients, for those who received a stent, a majority (62%) were given DAP and, for those who had a CABG, 53% were given SAP.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines recommend the use of aspirin and a thienopyridene, or ‘dual antiplatelet therapy’ (DAP) for the majority of patients following an acute coronary syndrome (ACS) [Vandvik et al 2012]. For the most part, physicians follow these recommendations [Zeymer et al 2013; Maier et al 2014; Potpara et al 2014; Knight et al 2015]. However, many ACS patients have comorbidities [e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation